PENGARUH PEMBERIAN BRAIN GYM TERHADAP KETERAMPILAN MOTORIK HALUS PADA ANAK PRASEKOLAH DI TK. KUMARA SARI VII DENPASAR BARAT - Anggareni Putu Ari (Coping: Community of Publishing in Nursing, 2014)
Brain Gym is one of the ways to maintain the brain fitness functionally, functional activity is done by stimulating brain centers through movements. Brain Gym movements can lead to increased blood flow in all parts of the brain, besides, it makes better and strengthen the relation between the two hemispheres of the brain. The purpose of this study was to determine the effect of brain gym on soft motor in preschool children. The design of this study was Quasi Experimental approach pre-test post-test with control group that provides therapeutic treatment brain gym in the experimental group while the control group was not given. Respondents in this study were aged 5-6 years amounted to 54 respondents were divided into two treatment groups and the control group. The independent variable in this study is brain gym while the dependent variable is a soft motor. The data were collated by using observation sheet. The data was analyzed by using the Wilcoxon Sign Ranks Test and Mann-Whitney Test. Based on the Wilcoxon Sign Ranks Test, obtained value (p) = 0,001 indicates Ha received and the Mann-Whitney Test the (p) 0,001. This means that there is a therapeutic effect of brain gym to increase soft motor skills of preschool children in the kindergarten Kumara Sari VII West Denpasar. It is recommended that teachers and parents to introduce and train the brain gym movements begin at an early age and are carried out routinely in order to obtain maximum results.